ECONOMICS OF EDUCATION: THE EXAMPLE OF THE BALKAN COUNTRIES - Ognjen Erić; Slaviša Kovačević; Jelena Bjelić; Dejan Molnar (Acta Economica)
Economic growth is an economic topic that attracts a lot of attention in science and research. This is a consequence of the emergence of increasingly frequent regional and global instabilities, which often develop into open economic crises of a larger scale. Therefore, today’s economic stability is largely threatened due to the slowdown in GDP growth. Economic growth is influenced by various economic factors, with education being one of the most important, which undeniably boosts productivity, competitiveness, and growth. Among the first, this topic was elaborated by Solow. In this research, regression analysis was used to analyze the influence of several selected variables that determine the state of education. The research results are presented in two models. The dependent variable is Gross National Income per capita (GNIpc), and the independent variables in the first model are years of education, macroeconomic stability, and ability to accept information technologies. In the first model, none of the independent variables is individually significant for the movement of GNIpc. The continuation of the analysis (second model) excludes the variable of macroeconomic stability. The final results are significant for the movement of GNIpc and show that an increase of one year in education leads to an increase in GNIpc by 4408 units, while an increase in the speed of ICT adoption leads to an increase in GNIpc by 543 units. Thus, the research results show a positive and significant influence of the selected independent variables on the economic growth of the Balkan countries.